The role of life satisfaction and living arrangements in the association between chronic disease and depression: a national cross-sectional survey - Shang, Zhao; Liu, Yuqing; Xue, Dongyu; Zheng, Yiping; Li, Yueping; Zhang, Baoquan; Dai, Yue (Frontiers in Psychology, 2023)
Introduction: For middle-aged and older people, depression is a frequent and prevalent illness. The purpose of this study was to examine the moderating function of living arrangements in the mediating model as well as the mediating role of life satisfaction in the association between chronic diseases and depressive symptoms.The China Health and Retirement Longitudinal Study (CHARLS) provided the data for this investigation (2018). Respondents were grouped according to depression status to compare the differences between middle-aged and older people with different depression statuses. The moderating effect of living arrangements and the mediating effect of life satisfaction were tested using the Bootstrap program and the simple slope approach.Results: The population's total prevalence of depressive symptoms was 30.3%.According to the mediating effect research, middle-aged and older people with chronic diseases experienced substantial direct effects on depressive symptoms (β=1.011, p<0.001). It has been established that life satisfaction has an 18.6% mediation effect between depressive symptoms and chronic diseases. Regarding the further moderating influence, it was discovered that chronic diseases had a more significant impact on the life satisfaction of middle-aged and older people who are in live alone than those who are living with others (β=0.037, p<0.05).In middle-aged and older people, chronic diseases have a major influence on depressive symptoms. Life satisfaction mediated the relationship between chronic diseases and depressive symptoms, and living arrangements moderated the first part of the route in the mediation model. Therefore, life satisfaction and living arrangements should be important considerations to decrease